PENGARUH TEMPERATUR DAN LAJU REGANGAN TERHADAP SIFAT MEKANIK MATERIAL SOLDER BEBAS TIMBAL Sn-3.0Ag-0.5Cu - Ananda Aransa, - (2020)
The purpose of this study is to investigate the mechanical characteristics of Sn-3.0Ag.0.5Cu (SAC305) lead free solder material under the influence of temperature and strain-rate. Tensile testing was carried out on SAC305 solder wires at temperatures of 20, 60, 90, 120, 150 ºC, for each temperature the strain-rate variation of 210-3 s-1, 210-4 s-1, 210-5 s-1. The data obtained based on tensile test results are processed in the form of stress-strain curves. The mechanical characteristics obtained are based on the stress-strain curve, namely yield strength, ultimate tensile strength, elastic modulus. The results obtained for temperatures 20, 60, 90, 120, 150 ºC at a strain rate of 2  10-4 s-1 are modulus of elasticity of 6.852103; 4,666103; 3,515103; 3,439103; 2,937103 MPa, for yield strength that is 10.2, 30.35; 13.69; 8.23; 2.5 MPa and ultimate tensile strength are 10.96; 31.07; 14.66; 9,20; 3.06 MPa. It can be seen that the trend shown by rising temperatures causes yield strength, ultimate tensile strength and elastic modulus to decrease, because at high temperatures, internal energy atoms are high, consequently the material atoms vibrate strongly with high thermal agitation. The relationship between modulus of elasticity is proportional to 1/Xo. The results obtained for strain-rate varied at a temperature of 20 ºC are 37.3; 10.2; 1.5 MPa and 38.19; 10,96; 2,017 MPa 1.8896×104; 6.852×103; 404.62 MPa. Based on the results obtained it can be concluded that temperature affects the mechanical properties of lead-free solder and the trend shows that all mechanical properties that have been evaluated decrease with increasing temperature. The strain rate affects the mechanical properties of lead-free solder, the pitch which is shown to be the opposite of the temperature influence trend, it is related to the deformation process that occurs. Keywords : Mechanical Properties, Temperature, Strain-rate, Lead-free solder, SAC30